PEMANFAATAN TEKNOLOGI INFORMASI DALAM PENGUATAN LAYANAN ADMINISTRASI KANTOR KELURAHAN BARRANG CADDI KOTA MAKASSAR - Sadly Samsuddin; Hasyrif Sy; Abdul Ibrahim; Arham Arifin; Madyana Patasik; Imran Djafar; Suci Ramadhani Arifin; Asmah Akhriana; Suryani Suryani; Nurdiansah Nurdiansah; Ahyuna Ahyuna; Usman Usman; Nurlina Nurlina; Faizal Faizal; Magfirah Magfirah (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Barrang Caddi Island is one of the islands located in Barrang Caddi Village, Sangkarang Islands District, Makassar City. The Barrang Caddi Village Office as a public service provider has various types of services to the community, including issuing recommendation letters and certificates. Barrang Caddi Village Office staffs were required to provide effective and efficient services to the community, hence village officials must always improve their knowledge and skills, including increasing information technology literacy. Utilization of information technology in supporting public services within the Barrang Caddi Village environment requires the ability of Human Resources to use this information technology. In response to this, the Dipa Makassar University Lecturer team carried out community service activities addressed to the Barrang Caddi Village officers with a counseling approach in the form of training in the use of office applications, namely Microsoft Word, Microsoft Excel and the internet. The purpose of this community service activity was to improve the quality of HR performance for the Barrang Caddi Village Office in operating office applications to ensure faster, more effective and efficient services for the community. Based on the results of the community service activities that have been carried out, it can be seen that all participants in the training, namely the Barrang Caddi Village Office staff, were very enthusiastic about participating in the training and the participants were able to understand and practice well all the material presented during the activity.